التجليات الحضارية للغة العربية وتأثيرها الحديث The cultural manifestations of the Arabic language and its modern impact - Ali, Asem Shehadeh Saleh (2019)
تناولت الدراسة الأبعاد الحضارية للغة العربية في ضوء مفهوم الحضارة في الأدبيات المعاصرة عند الحديث عن مفاهيم مختلفة تتعلق بمصطلح حضارة، ومعانيه اللغوية والاصطلاحية، وهناك علاقة قوية بين اللغة العربية بوصفها لغة القرآن الكرم، وبين الحضارة الإسلامية، أساسها العقيدة الإسلامية، فهناك فكرة الاكتساب اللغوي للغة العربية من غير الناطقين بها، وتعلمهم إياها وإتقانهم لها ونشرها بين المسلمين ونشأة العلوم الإسلامية، و اللغة العربية تحمل التراث المجتمعي وتقوم بربط أفراده بعضهم ببعض، وتهيئ الفرصة للتفاعل فيما بن أفراد المجتمع الواحد في إطار الود والتلاقي والتفاهم؛ فالذين يتكلمون لغة واحدة تكون العلاقة فيما بينهم علاقة قوية ومتينة، واللغة أساس لتوحيد الكلمة وبناء الوطنية في الدول الإسلامية وغيرها من الدول الأوروبية، والفعل الحضاري للغة هو مجموع الأنشطة اللغوية التي تقوم بتحقيق التفاعل اللغوي بين الأفراد وبين الموجودات أو الكائنات في الحياة، وهي تعبر عن الشهود الحضاري في تحقيق فعل هذه الجماعة في بناء الحضارة البشرية عبر التفاعل بين الأفراد والأشياء والأفكار، وبالتفعيل الحضاري يتمّ تجديد الفعل الحضاري اللغوي وتمكين اللغة العربية وتنشيطها للإسهام بشكل مباشر في البناء الحضاري وتطويره والمحافظة عليه. The cultural manifestations of the Arabic language and its modern impact Abstract The study deals with the cultural dimensions of the Arabic language in the light of the concept of civilization in modern literature when talking about different concepts related to the term of civilization and its linguistic and theological meanings. There is a strong relationship between Arabic as the language of the Holy Qur'an and Islamic civilization, Arabic and non-Arabic speakers, and their learning and mastery of Arabic language, and dissemination among Muslims and the emergence of Islamic sciences. Arabic language carries the community heritage, connect the members between each other, and provide the opportunity to interact with the members of the community within the framework of friendliness. The language is the basis for the unification of the word and the building of patriotism in Islamic countries and other European countries, and the cultural act of language is the sum of linguistic activities that achieve the linguistic interaction between individuals and assets or objects in life. It expresses the civilizational witnesses in the realization of the action of this group in building human civilization through the interaction between individuals and objects and ideas. The civilizational activism, the renewal of the civilizational linguistic act and the empowerment of the Arabic language and its activation contribute directly to the civilizational building and development.